Chemical Composition and Consumer Acceptance of Balinese Snake Fruit during Marketing - ID. A.G Lidartawan; Didik Purwadi; Sri Anggrahini (Indonesian Food and Nutrition Progress, 2002)
The research has been conducted baSed on chemical composition and consumer acceptance to Balinese Snake Fruit during marketing through three retailers, i.e., traditional markets, fruit shop and superinarkets within the province of Bali. This research was conducted with laboratory research. The sampling was conducted using the stratified random sampling. Balinese Snake fruit that are sold in fruit shops have the best quality with a chemical composition of water content 83.91%, acid content 3.56% db, total sugar content 84.54% db, total content of tannin 1.07% db, fruit size relatively larger (average 13 fruits/kg), panelist acceptance of color 6.90 (between "rather like" and "like') scale, aroma 6.90 (between "rather like" and "like"), texture 6.70 (between "rather like" and "like"), taste 6,95 (between "rather like" and "like '), and total acceptance of 6.95 (between "rather like" and "like') scale.